Problematika Pada Tataran Pembelajaran Sejarah Sastra - Irfan Juhari; Eponiah Eponiah; Heri Isnaini (Universitas Palangka Raya, 2023)
Problems are often associated with various problems, but the essence of problematics is to find the best solution with supporting things. Learning the history of literature itself is learning about the origins of or relating to the past about literature. Learning literature from time to time changes and adds to the level of study that is applied, giving rise to various problems in the context of its teaching of both formal and non - formal education. The problems themselves arise from various factors, the quality of learning literature in schools which may be caused by various things such as the curriculum, teachers, students, facilities and infrastructure, and perhaps also from the approach to learning literature itself, and the lack of deepening of the history of literature learning. Thus, to find a solution there is a literature study, including making the school a literary field, innovative learning with changes that are adjusted to the passage of time, as well as various learning approaches in the context of applying the teaching of literary history.